2017
DOI: 10.1002/jcop.21855
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and depression in home visiting clients: Home visitor perspectives on addressing clients’ needs

Abstract: Substance use and depression are prevalent among mothers enrolled in home visiting programs and are significant risk factors for child maltreatment, yet most home visiting programs are staffed by workers who lack the training and clinical skills to address these risks. Emanating from one state network's interest in advancing its practice in this area, the current study surveyed 159 home visitors on their current practices, training, knowledge, and perceived self‐efficacy, and perceived system‐ and client‐level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Home visiting professionals have given motivational communication techniques increased attention (e.g., Dauber, John, Hogue, Nugent, & Hernandez, ; Olds et al., ; Silovsky et al., ). A randomized controlled trial showed that training nurses in motivational interviewing techniques and giving them latitude to adjust the frequency and content of visits led to greater retention and more completed home visits (Olds et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Home visiting professionals have given motivational communication techniques increased attention (e.g., Dauber, John, Hogue, Nugent, & Hernandez, ; Olds et al., ; Silovsky et al., ). A randomized controlled trial showed that training nurses in motivational interviewing techniques and giving them latitude to adjust the frequency and content of visits led to greater retention and more completed home visits (Olds et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Home-based family support programs are a key intervention to promote positive parenting and attachment, prevent child maltreatment, and facilitate linkage to community resources for high-risk families (Azzi-Lessing 2013 ). Home visiting models typically target pregnant and postpartum women with risk factors known to disrupt the parent–child relationship, such as history of trauma; intimate partner violence; mental health issues, including maternal depression; low academic achievement, often leading to low income; and a limited support network (Ammerman et al 2015 ; Dauber et al 2017a , b ). Maternal substance use is another known risk factor for child maltreatment and may be a comorbidity among at-risk populations (Connelly et al 2013 ; Dauber et al 2017a , b ; Michalopoulos et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Few home visiting models, however, are equipped to address the complex needs of families affected by maternal substance use. Substance use among families receiving home visiting services has been associated with reduced program engagement and diminished outcomes (Azzi-Lessing 2013 ; Dauber et al 2017a , b ; Green et al 2018 ). Many home visiting programs do not conduct systematic data collection related to substance use indicators, and few focus on substance use-related outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a national sample, 26% of HV clients reported prior binge drinking, 13% reported past illicit drug use, 34% reported clinically significant depression symptoms, and 17% reported past-year physical or psychological IPV (Michalopoulos et al, 2015). Despite the potential of HV to improve access to behavioral health treatment, studies have demonstrated low rates of identification of SU, MD, and IPV and referral to treatment within HV (Dauber et al, 2017; Duggan et al, 2004; Tandon, Parillo, Jenkins, & Duggan, 2005), and more difficult engagement and poorer outcomes for families with complex risk profiles (Azzi-Lessing, 2013; Damashek, Doughty, Ware, & Silovsky, 2011; Eckenrode et al, 2000). …”
Section: Introductionmentioning
confidence: 99%